Behavioral outcome in congenital shunted hydrocephalus without spina bifida - Helder, Emily J.; Austria, Emily; Lacy, Maureen; Frim, David M. (Journal of Pediatric Neurology, 2011)
Neuropsychiatric disease is often prevalent in white matter disorders. Hydrocephalus, for example, causes a disruption of white matter pathways. While research has shown that emotional and behavioral problems are prevalent in myelomeningocele (MMC) associated hydrocephalus, it is less clear if this is true in hydrocephalus due to other etiologies. The present study compared 30 children with early onset communicating shunted hydrocephalus with 18 healthy controls (age range 6–16 years) with regard to parent rated behavior and emotional functioning, controlling for intelligence quotient differences between groups. Results indicated that children with communicating hydrocephalus have a higher incidence of clinically significant reported behavioral/emotional difficulties (30%) compared with controls (11%). Internalizing problems were significantly more common in patients compared to controls. These findings underscore the importance of monitoring behavioral and emotional adjustment in children with hydrocephalus and intervening as appropriate. In addition, these observations show that MMC children with hydrocephalus and congenital hydrocephalus patients have similar emotional difficulties implying that it is hydrocephalus and not other MMC-associated brain anomalies that affect emotional outcome.
Keywords: Congenital hydrocephalus; internalization; emotional problems